Influence of the Quality of the Opponent on Physical, Technical, and Tactical Performance of Elite Female Soccer Players in International Competitions - Morales-Acuna, F (SPRINGERNATURE, 2024)
Purpose Soccer is a complex sport that depends on several physical performance and technical-tactical factors. Therefore, we aimed to: i) analyze the differences in physical, technical, and tactical performance of one international team when competing against opponents divided by their world ranking (i.e., higher ranked [HR] and lower ranked [LR]) ii) explore the associations between physical, technical, and tactical measures obtained when playing against HR and LR teams. Methods Twenty-seven elite female soccer players (n = 27; age: 27 +/- 3.4 years; height: 162.8 +/- 4.32 cm; body mass: 60.5 +/- 4.6 kg) selected from a South American international team during 34 official FIFA matches volunteered to participate in this study. Physical measurements were recorded using Global Positioning System (Catapult Sports (R), 10 Hz), and the post-match rate of perceived exertion (RPE) was also reported. Technical and tactical variables were recorded through an analysis platform (InStat Footbal (R)). Results When compared to LR, HR matches showed significantly trivial to moderate higher RPE, total distance (TD), meters per minute (MM), and player load (PL) (p < 0.001) and small to moderate lower rates in the number of passes and effectiveness (p < 0.001). Furthermore, small to moderate correlations (p = 0.026) were observed for LR and HR matches during the offensive and defensive phases. Conclusion Physical, technical, and tactical performance are significantly affected by the opponents ranking. Furthermore, the relationships observed between the physical, technical, and tactical factors indicates that physical performance has a similar effect on technical and tactical variables, regardless of the level of opposition.